AB0900 A Short, Quick, and Easy Questionnaire to Estimate Daily Dietary Calcium Intake of Osteoporosis Patients. (9th June 2015) - Rasch, L.A.; de van der Schueren, M.A.E.; van Tuyl, L.H.D.; Bultink, I.E.M.; Lems, W.F.
Abstract : Background: Calcium supplements are widely used for the prevention and treatment of osteoporosis. However, recent literature suggests that too much calcium supplementation may be associated with cardiovascular events (1). For this reason, calcium supplementation should be based on actual and adequate dietary calcium intake. A previously designed calcium intake list appeared to be invalid (2) and other alternatives are too time consuming for clinical practice. Therefore, we developed a new calcium intake list, to accurately estimate dietary calcium intake, which was validated in this study. Objectives: The aim of this study is to validate a short, quick, and easy calcium intake list, to be able to estimate dietary calcium intake, with an extensive dietary history (DH) as a reference method. Methods: This cross-sectional study included consecutive patients attending the outpatient rheumatology department at the VUmc in Amsterdam, the Netherlands, for the treatment of primary or secondary osteoporosis. Based on the food groups which contribute most to daily dietary calcium intake and portion sizes determined from our earlier validation study (2), a short three-item calcium intake list was designed. As a reference method, an extensive DH with specific focus on calcium products and extra attention for portion sizes was performed. Before starting the study, a difference of 250 mg calcium or more between both methods was determined as clinically relevant. Performing the short calcium intake list took about 3 minutes, performing the DH took 60 minutes. Results: In this study, 66 patients with primary (n=40) and secondary (n=26) osteoporosis were included. The three-item calcium intake list showed a small, clinically non-relevant, difference with the DH of 25±350 mg calcium per day (p=0.568), see table 1 . Sensitivity and specificity of the short calcium intake list, compared to the DH, were respectively 73% and 80%. In 50% of the individuals, a clinically relevant difference of 250 mg calcium or more was observed between the calcium intake list and the DH, while in 17% a difference of 500 mg or more was observed. Conclusions: The short calcium intake list is a three-item, quick and easy questionnaire to accurately estimate dietary calcium intake of osteoporosis patients at a group level, and thus very helpful for clinical studies. However, in individual patients, clinicians should be aware of not identifying a deficient calcium intake in approximately 20% of the patients, and of prescribing supplements to patients with a sufficient intake in approximately 30% of patients. Remarkably, mean calcium intake is around the current Dutch recommendation of 1000-1200 mg calcium per day. This indicates that a large proportion of the osteoporosis patients might not even need calcium supplementation. References: Bolland MJ, et al. BMJ 2010. (2) Rasch LA, et al. Austin J Nutri Food Sci 2014. Disclosure of Interest: None declared